Efficacy of laser remodeling in the genitourinary syndrome of menopause: A review - Mekan R. Orazov; Elena S. Silantyeva; Viktor E. Radzinsky; Liudmila M. Mikhaleva; Elizaveta A. Khripach; Evgeny D. Dolgov (IP Berlin A.V., 2023)
The real-world treatment of genitourinary syndrome of menopause has several limitations: contraindications to topical estrogen therapy, which is currently recognized as the "gold standard" treatment for vulvovaginal atrophy (VVA), fear of the systemic effects of topical estrogens or/and carcinophobia, and poor compliance of patients to intravaginal agents. Therefore, there is an unmet need for alternative noninvasive or minimally invasive therapies, mostly non-hormonal. A PubMed, Cochrane Library, Science Direct, and ELibrary databases were searched for the keywords CO2-laser, Er:YAG-laser, vulvovaginal atrophy, genitourinary syndrome of menopause, treatment, postmenopausal age for 20122022. Remodeling microablative laser therapy using carbon dioxide (CO2) is a promising method for treating VVA, acting pathogenetically and symptomatically. CO2 laser relieves VVA symptoms and improves the condition of the vaginal mucosa by enhancing regeneration and restoring vaginal pH. However, evidence of the efficacy and long-term safety of the method, obtained in high-quality studies, is needed before the method can be introduced into widespread clinical practice. Aim. To analyze and summarize the evidence-based and experimental data on the efficacy and safety of laser therapy for VVA and genitourinary syndrome of menopause.